2005
DOI: 10.1002/jcu.20137
|View full text |Cite
|
Sign up to set email alerts
|

Duplex sonography of retro-orbital and carotid arteries in patients with normal-tension glaucoma

Abstract: In patients with symmetric normal-tension glaucoma, duplex sonography showed an elevated RI in CRA and PCA. The Doppler evaluation of carotid arteries was useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Doppler US has been recognized in many papers as an effective tool to assess alteration in these flow dynamics [12, 13, 15]. Most of published studies include healthy patients without glaucoma risk factors as controls and patients with well-established glaucomatous damage as cases, while our population was performed by subjects with risk factors for glaucoma, but without yet established visual field impairment (<−5 dB of MD).…”
Section: Discussionmentioning
confidence: 99%
“…Doppler US has been recognized in many papers as an effective tool to assess alteration in these flow dynamics [12, 13, 15]. Most of published studies include healthy patients without glaucoma risk factors as controls and patients with well-established glaucomatous damage as cases, while our population was performed by subjects with risk factors for glaucoma, but without yet established visual field impairment (<−5 dB of MD).…”
Section: Discussionmentioning
confidence: 99%
“…CDI has been recognized in many studies as a useful modality to assess alteration in orbital blood flow dynamics. [11][12][13] Authors have analysed flow indices in ophthalmic artery and CRA. The posterior ciliary arteries are small caliber vessels and due to their direction, variable intonation angles are usually required for their analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The CDI imaging was carried out using Philips HD5 scanner using high frequency probe (10)(11)(12). In each eye, Peak systolic Velocity(PSV), End Diastolic Velocity (EDV) and Resistivity index (RI) of OA and CRA.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to several problems, it is difficult to accurately and directly measure the ocular blood flow in real time. Many previous studies have suggested that CDI can assess the changes in ocular hemodynamics [13,[31][32][33]. Although CDI can monitor the ocular blood flow velocity in real time, it indirectly detects the blood flow of large arteries that supply the eyes instead of the blood flow in the ocular microvessels.…”
Section: Discussionmentioning
confidence: 99%